2018
DOI: 10.1097/jom.0000000000001365
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Heat-Related Illness in U.S. Workers

Abstract: Severe HRI is more likely when personal susceptibilities coexist with work-related and environmental risk factors. Almost all HRIs occur when employers do not adhere to preventive guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Pre-existing illness, a high BMI and CVDs can predispose individuals to HS [7]. Common clinical findings in patients with HS include multiple organ failure, rhabdomyolysis and systemic inflammation [6]. Patients with HS frequently have decreased diastolic blood pressure and oxygen saturation, an increased shock index and a reduced consciousness level [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-existing illness, a high BMI and CVDs can predispose individuals to HS [7]. Common clinical findings in patients with HS include multiple organ failure, rhabdomyolysis and systemic inflammation [6]. Patients with HS frequently have decreased diastolic blood pressure and oxygen saturation, an increased shock index and a reduced consciousness level [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HRIs present to the emergency department frequently, and the visit rates are correlated with temperature anomalies [2]. Severe HRIs can cause multiple organ failure, rhabdomyolysis and coma with acute and even permanent damage to the vital organs [36]. Heat stroke (HS) is the most severe HRI and has been defined as a patient with profound central nervous system abnormalities and severe hyperthermia (core temperature typically but not always > 40°C) [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, although some states have state‐specific heat standards and current federal recommendations are comprehensive, studies suggest there is limited adoption of these practices. An investigation of 84 OSHA heat enforcement cases (i.e., heat illness and fatality reports) reported that 80% of employers did not rely on national standard approaches for heat illness prevention (Tustin, Cannon, et al., 2018 ; Tustin, Lamson, et al., 2018 ). Moreover, heat enforcement cases lacked at least one or more core components of a heat safety plan (e.g., heat acclimatization [HA]) (Tustin, Cannon, et al., 2018 ; Tustin, Lamson, et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of 84 OSHA heat enforcement cases (i.e., heat illness and fatality reports) reported that 80% of employers did not rely on national standard approaches for heat illness prevention (Tustin, Cannon, et al., 2018 ; Tustin, Lamson, et al., 2018 ). Moreover, heat enforcement cases lacked at least one or more core components of a heat safety plan (e.g., heat acclimatization [HA]) (Tustin, Cannon, et al., 2018 ; Tustin, Lamson, et al., 2018 ). Similarly, a study reported that among 25 outdoor occupational heat‐related illnesses, 14 fatalities and 11 nonfatal illnesses occurred when occupational heat exposure limits (OELs) were exceeded (Tustin, Cannon, et al., 2018 ; Tustin, Lamson, et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amphetamines are central nervous system stimulants that can induce hyperthermia independently or in combination with other risk factors (2). During 2010-2016, the Directorate of Technical Support and Emergency Management's Office of Occupational Medicine and Nursing (OOMN), at the Occupational Safety and Health Administration (OSHA), identified three workers with fatal hyperthermia who tested positive for methamphetamine (3). To identify additional cases of severe hyperthermia in which workers tested positive for amphetamines, and to support OSHA's enforcement activities, OOMN reviewed all medical records and investigation materials submitted by other OSHA offices to OOMN during January 1, 2010-August 31, 2019.…”
mentioning
confidence: 99%